Implicit Philosophy of Love in the Antiquity: An Attempt to Rethink - Turenko, Vitali (Studia Warmińskie, 2017)
It proved the position according to which, in the study of a particular “words of love” in Ancient Greek or Latin Dictionaries, it must indicate in what period, what form of cultural heritage (literature, geography, history, philosophy, etc.) his used. This approach, in opinion of author, be able to give a more objective and complete picture of a particular understanding of the diversity of one or the other “word of love”. It was revealed that in the study of the philosophical understanding of love, amorousness, friendship is must not limited to the classical works of Plato (Symposium, Phaedrus, Lysis) and Aristotle (ethical works of Stagirite) in the context of these phenomenons. This methodological position will allow for the understanding of the evolution of the views of both the Titans of Greek philosophy, as well as avoiding any “prejudices” that the matter can be found in the pages of some of the scientific research. It is noted that among the philosophical heritage of ancient civilization on the phenomenon of love is not enough studied of fragments of the early Greek philosophers (notably anthropological aspect of love), the Sophists and the Socratic schools, as well as treatises of representatives schools of the Hellenistic period.